ANALYSIS OF REGENT'S LEADERSHIP BANYUWANGI DISTRICT 2010-2020 PERIOD (ABDULLAH AZWAR ANAS) - Kapiso, Pian; Ansar, Ansar (Universitas Negeri Gorontalo, 2022)
This paper describes the need for innovative leadership. The moral degradation that undermines the foundations of the life of the nation and state, as well as the development of Corruption, Collusion, and Nepotism (KKN) as evidence of the severity of moral degradation, has almost plunged the Unitary State of the Republic of Indonesia (NKRI) into the abyss of destruction. The presence of innovative leaders is a breath of fresh air for the leadership crisis and public distrust. Shows concern, despite facing challenges and threats from various parties. This paper, using the library research method supported by reading literature and secondary data, is then compiled, and analyzed so as to produce conclusions that can be accounted for. Leadership innovation needs exemplary, courage and the ability to change mindsets to improve people's welfare.